2012
DOI: 10.4161/viru.19077
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteins modulate lipopolysaccharide and lipoteichoic acid-induced activation and contribute to the clinical outcome of sepsis

Abstract: Keywords: sepsis, serum proteins, LPS, LTABacterial cell wall components, such LPS and LTA, are potent initiators of an inflammatory response that can lead to septic shock. The advances in the past were centered around membrane-bound receptors and intracellular events, but our understanding of the initial interactions of these bacterial components with serum proteins as they enter the bloodstream remain unclear. In this study we identified several serum proteins, which are involved in the innate recognition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Because this interaction results in cell wall distortion‐disruption and exposes bacteria to osmotic shock, such cationic polysaccharides are considered potent (<200 ppm) antimicrobials against Gram‐positive bacteria, such as Staphylococcus aureus and Listeria monocytogenes , and, at higher concentrations, against Lactobacilli (Goy and others ), while oleoyl‐chitosan nanoparticles (a more lipophilic particle) inhibit Escherichia coli and S. aureus by damaging the cell membrane and other intracellular targets (Xing and others ). Triantafilou and others () demonstrated that blood proteins such as apolipoproteins, LDL, and transferrin inactivate LTA, reducing its proinflammatory potential. This finding may indicate that dietary proteins can also bind to LTA, reducing or facilitating bacterial release within the GI tract.…”
Section: Cell Adhesion and Functional Group Interactionsmentioning
confidence: 99%
“…Because this interaction results in cell wall distortion‐disruption and exposes bacteria to osmotic shock, such cationic polysaccharides are considered potent (<200 ppm) antimicrobials against Gram‐positive bacteria, such as Staphylococcus aureus and Listeria monocytogenes , and, at higher concentrations, against Lactobacilli (Goy and others ), while oleoyl‐chitosan nanoparticles (a more lipophilic particle) inhibit Escherichia coli and S. aureus by damaging the cell membrane and other intracellular targets (Xing and others ). Triantafilou and others () demonstrated that blood proteins such as apolipoproteins, LDL, and transferrin inactivate LTA, reducing its proinflammatory potential. This finding may indicate that dietary proteins can also bind to LTA, reducing or facilitating bacterial release within the GI tract.…”
Section: Cell Adhesion and Functional Group Interactionsmentioning
confidence: 99%
“…Liu, Yu, Chai, and Zhu (2012) suggested that transferrin has a role in activating the antimicrobial activity of macrophages or inducing strong pro-inflammatory responses. More importantly, transferrin was found as a major lipopolysaccharide binding protein, acting as a neutralizing agent (Berger, Schleich, Seidelmann, & Beger, 1991;Triantafilou et al, 2012), suggesting its inhibitory effect on LPSinduced inflammatory responses. Transferrin significantly evoked the killing activity of goldfish macrophages subjected to different pathogens or pathogen products including LPS (Stafford & Belosevic, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There are many LTA-binding proteins, as follows: LBP, CD14, mannose-binding protein, L-ficolin, albumin [6,31,32,33], apolipoproteins A and C [34], transferrin and hemoglobin [35,36], high- and low-density lipoproteins [37], hemoglobin subunits α and β and S100A9 and SPLUNC2 [38]. Until now, however, LBP was the only molecule known to mediate the transfer of LTA to CD14 to enhance the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%